TRADISI BAWA DULANG SEBAGAI LIVING HADIS DALAM MASYARAKAT SASAK DESA SETUTA LOMBOK TENGAH - Evi Sulfaningsih; Nurhadi Nurhadi; Eko Suwanto; Baha Shofa Mijdal; Abdul Latif (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines the bawa dulang tradition as a form of living hadith in the Sasak community of Setuta Village, Central Lombok. Bawa dulang is a food-sharing practice performed during various social and religious occasions, such as weddings, circumcisions, and Islamic commemorations. This research aims to analyze the practice of bawa dulang, reconstruct the hadith values embodied in it, and explore how the community receives and understands the teachings of the Prophet Muhammad. This study employs a qualitative approach using observation, in-depth interviews, and documentation. Informants consist of religious leaders, traditional leaders, and local residents. Data were analyzed descriptively and interpretively within the framework of living hadith. The findings indicate that the community perceives bawa dulang not merely as a cultural custom but as part of Islamic practice related to sharing, almsgiving, honoring neighbors, and strengthening social ties. These hadith values are not understood textually but are substantively internalized through social experience and religious instruction. The practice also reflects gendered participation, with women playing a central role in religious rituals, while men represent households in social events.